2006
DOI: 10.1111/j.1365-2958.2006.05114.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, functional expression and characterization of Mesorhizobium loti arylamine N‐acetyltransferases: rhizobial symbiosis supplies leguminous plants with the xenobiotic N‐acetylation pathway

Abstract: SummaryArylamine N -acetyltransferases (NATs) are xenobiotic-metabolizing enzymes involved in the detoxification of numerous aromatic chemicals. The NATdependent N-acetylation pathway has not previously been detected in plants. We demonstrate here the occurrence of the NAT-dependent pathway in leguminous plants, due to symbiosis with Mesorhizobium loti . We cloned two NAT enzymes from M. loti and showed that these two recombinant enzymes catalysed the N-acetylation of several known NAT substrates, including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…The catalytic efficiency of PaNat1 with 3,4-DCA was 2.5 times higher and that of PaNat2 was five times higher than that of the Pseudomonas aeruginosa NAT, which is currently considered to be the most efficient NAT enzyme ever described, particularly with 3,4-DCA (29). When compared with the two NAT isoforms from the plant symbiotic bacterium Mesorhizobium loti, the catalytic efficiency toward 3,4-DCA by PaNAT2 (k cat /K m ϭ 17,400 M Ϫ1 ⅐s Ϫ1 ) was 220 and 120 times higher than that of M. loti NAT1 and M. loti NAT2, respectively (14).…”
Section: Identification and Characterization Of P Anserina Nat Enzymmentioning
confidence: 99%
See 3 more Smart Citations
“…The catalytic efficiency of PaNat1 with 3,4-DCA was 2.5 times higher and that of PaNat2 was five times higher than that of the Pseudomonas aeruginosa NAT, which is currently considered to be the most efficient NAT enzyme ever described, particularly with 3,4-DCA (29). When compared with the two NAT isoforms from the plant symbiotic bacterium Mesorhizobium loti, the catalytic efficiency toward 3,4-DCA by PaNAT2 (k cat /K m ϭ 17,400 M Ϫ1 ⅐s Ϫ1 ) was 220 and 120 times higher than that of M. loti NAT1 and M. loti NAT2, respectively (14).…”
Section: Identification and Characterization Of P Anserina Nat Enzymmentioning
confidence: 99%
“…Certain fungi and bacteria have nonetheless been shown to biotransform 3,4-DCA to its acetylated form (19,34). In the bacterium M. loti, a NAT isoform has been shown to acetylate 3,4-DCA (14). In plants, glucosylation of 3,4-DCA was described, but this pathway was considered as non-effective at detoxifying this AA (35).…”
Section: Detoxification Of the Highly Toxic Pesticide Residue 34-dcamentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have focused on conversion of 3,4-DCA into its acetylated form. First, it has been shown that acetylated 3,4-DCA is less toxic than 3,4-DCA; second, some soil bacteria and fungal strains acetylate 3,4-DCA 12,13 . Although aniline derivatives undergo complex transformations in soils, these studies open up new possibilities in bioremediation.…”
mentioning
confidence: 99%